Management of IgA Nephropathy in Pediatric Patients - Sophie Schroda; Martin Pohl (MDPI AG, 2022)
The onset of IgA nephritis in childhood and adolescence often develops into chronic glomerulonephritis with declining renal function. Although these long-term consequences are known, there is still a lack of evidence-based treatment recommendations in this age group. We report data from 22 pediatric patients who were biopsied to confirm the diagnosis of IgAN at our clinical center. 14 of them were treated with corticosteroids according to the recommendations for IgA nephritis vasculitis of the German Society of Pediatric Nephrology (GPN). Improvement was achieved in the majority of all cases, with a significant reduction in proteinuria five months after initiation of therapy. Our data suggest that treatment regimens for acute IgA nephritis and IgA vasculitis nephritis may be unified and are discussed in the context of current studies.